2022
DOI: 10.3390/ijerph19063745
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemic on Pediatric Physician Wellness: A Cross-Sectional Study

Abstract: The COVID-19 pandemic has provided challenges to all healthcare workers. While the brunt of treating COVID-19 patients fell upon adult providers, pediatricians also experienced significant stressors and disruptions. Academic pediatricians and trainees (fellows and residents) were redeployed to manage adult patients in hospitalist and intensive care settings and/or had major changes to their clinical schedules. In this study, we aimed to describe levels of self-reported depression, anxiety, and burnout in pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…During the COVID-19 pandemic, burnout was found to be higher in physicians and nurses than in other health care workers. 51 - 54 The findings of the present study showed that burnout is negatively related to work engagement. Findings from a survey of 212 health care workers in a Norwegian hospital found that emotional exhaustion had direct effects on job attitudes (job satisfaction and organizational engagement).…”
Section: Discussionmentioning
confidence: 49%
“…During the COVID-19 pandemic, burnout was found to be higher in physicians and nurses than in other health care workers. 51 - 54 The findings of the present study showed that burnout is negatively related to work engagement. Findings from a survey of 212 health care workers in a Norwegian hospital found that emotional exhaustion had direct effects on job attitudes (job satisfaction and organizational engagement).…”
Section: Discussionmentioning
confidence: 49%
“…Future studies should continue exploring the protective role of resilience and organizational support to identify interventional targets that address mental health outcomes of physicians. Future studies should also include the trajectories and longitudinal mental health impacts of physicians and other HCWs at the front lines of the COVID pandemic, particularly nurses, who typically have greater direct patient care involvement than physicians, and physician trainees, who have been shown to be particularly vulnerable to COVID-related stressors ( 5 , 49 ). Finally, future work should continue the evaluation of the many interventions directed at frontline care delivery, health care organization, external environment, individual mediating factors to address clinician burnout and other adverse mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies that have used the EPII have summed participants’ responses to the items to create subscales and/or to create a total score of negative pandemic impacts and a total score of positive pandemic impacts (Belfer et al, 2022; Doom et al, 2021; Haydon & Salvatore, 2021; Hezel et al, 2022; Mayorga et al, 2022; Porter et al, 2021; A. Shah et al, 2021; Stone et al, 2021) or created a proportion score (Hussong et al, 2022), even in studies with large sample sizes (e.g., Doom et al, 2021; Haydon & Salvatore, 2021).…”
Section: Development Of the Epiimentioning
confidence: 99%
“…For instance, if an individual were to endorse “yes, me” and “no” response options for one item, the item would not be scorable. The most common method of scoring the EPII (referred to as Scoring Method 1 below) involves dichotomizing the responses by collapsing “yes, me” and “yes, person in home” into one category, and collapsing the “no” and “NA” responses into a second category (Belfer et al, 2022; Doom et al, 2021; Haydon & Salvatore, 2021; Hezel et al, 2022; Mayorga et al, 2022; Sargent et al, 2022; A. Shah et al, 2021; Stone et al, 2021).…”
Section: Development Of the Epiimentioning
confidence: 99%
See 1 more Smart Citation